Career as a cameraman - Memorial University of Newfoundland. Extension Service (Producer) (MUN Extension Service, 1975)
Derek Kennedy, a cameraman working for the CBC, describes his experience in becoming a cameraman - the good things abut the job and some of the bad experiences he has had in the past. Hosted by Norah Fitzpatrick. Video cuts out briefly in the middle tracking is poor in places